Negative electrode layer
By employing Si-based particles with tailored diameter and peak intensity ratios, the negative electrode layer in all-solid-state batteries addresses resistance issues in high SOC regions, improving battery performance through controlled volume changes.
Patent Information
- Application Number
- JP2024166878
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-11-29
AI Technical Summary
Si-based negative electrode materials in all-solid-state batteries experience increased resistance in high State of Charge (SOC) regions due to large volume changes during charging and discharging, which are partially mitigated by voids but result in higher battery resistance.
A negative electrode layer containing Si-based particles with specific particle diameter ratios (D90/D50 ≥ 37.9) and peak intensity ratios (D2/D1 ≤ 0.30) is used, incorporating pores to manage volume changes and reduce resistance.
The specified Si-based particle characteristics lead to a negative electrode layer with reduced resistance in high SOC regions, effectively managing volume changes and enhancing battery performance.
Smart Images

Figure 2024174051000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to anode layers for use in all-solid-state batteries. [Background technology]
[0002] An all-solid-state battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries having an electrolyte solution containing a flammable organic solvent. In addition, Si is known as a negative electrode active material used in all-solid-state batteries. For example, Patent Document 1 discloses an all-solid-state battery in which the negative electrode active material layer has voids in a region of 0.3 μm around the surface of the Si-based negative electrode active material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-103656 A Summary of the Invention [Problem to be solved by the invention]
[0004] Si has a large theoretical capacity and is effective in increasing the energy density of all-solid-state batteries. On the other hand, Si has a large volume change during charging and discharging, which may cause fluctuations in the confining pressure of the all-solid-state battery. In this regard, although the volume change of Si can be suppressed by providing voids as in Patent Document 1, a new problem arises in that the battery resistance increases in a high SOC (State of Charge) region.
[0005] The present disclosure has been made in view of the above circumstances, and has as its main object to provide a negative electrode layer having low resistance in a high SOC region. [Means for solving the problem]
[0006] In order to solve the above problems, the present disclosure provides a negative electrode layer for use in an all-solid-state battery, the negative electrode layer containing Si-based particles having pores as a negative electrode active material, the ratio (D90 / D50) of a particle diameter D90 of the Si-based particles to a particle diameter D50 of the Si-based particles being 37.9 or more, and the Si-based particles having a 1050 cm -1 Peak A and 1400 cm -1 and a peak B in the vicinity of the peak A, and the ratio (D2 / D1) of the intensity D2 of the peak B to the intensity D1 of the peak A is 0.30 or less.
[0007] According to the present disclosure, the Si-based particles having pores have a predetermined particle size ratio and peak intensity ratio, and therefore the negative electrode layer has low resistance in a high SOC region. Effect of the Invention
[0008] The present disclosure has an effect of providing a negative electrode layer having low resistance in a high SOC region. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a Si-based particle according to the present disclosure. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 3] 1 is a graph plotting shape parameters (D90 / D50) and surface characteristic parameters (D2 / D1) in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The negative electrode layer in the present disclosure will be described in detail below.
[0011] The negative electrode layer in the present disclosure is used in an all-solid-state battery and contains Si-based particles having fine pores as a negative electrode active material. The ratio (D90 / D50) of the particle diameter D90 of the Si-based particles to the particle diameter D50 of the Si-based particles is 37.9 or more. In addition, the Si-based particles have a 1050 cm -1 Peak A and 1400 cm -1 The ratio (D2 / D1) of the intensity D2 of peak B to the intensity D1 of peak A is 0.30 or less.
[0012] According to the present disclosure, the Si-based particles having pores have a predetermined particle size ratio and peak intensity ratio, and therefore the negative electrode layer has low resistance in a high SOC region.
[0013] As described above, when Si having voids (pores) is used, the volume change during charging and discharging can be suppressed, but the resistance in the high SOC region increases. In this regard, it is unclear what parameters of Si-based particles having pores (also called porous Si-based particles) contribute to reducing the battery resistance, and there is room for improvement in the performance of all-solid-state batteries using porous Si-based particles as the active material. The present inventors have focused on the shape parameters and surface characteristic parameters of porous Si-based particles and conducted repeated studies. As a result, they found that the battery resistance in the high SOC region can be reduced by adjusting the particle size ratio and the peak intensity ratio obtained by FT-IR to a predetermined range.
[0014] In the present disclosure, the exact reason why the resistance in the high SOC region is low is unclear, but it is presumed as follows. In Si particles having pores (porosity), it is considered that for a certain amount of pores, particles with a large particle size have higher lithium diffusivity inside the active material (Si particles) than particles with a small particle size. Therefore, it is considered that the resistance can be reduced by making D90 / D50 sufficiently large in Si-based particles. Also, it is considered that the resistance increases when the amount of Si-R bonds relative to Si-O bonds is large on the surface of the Si particles. Therefore, it is considered that the resistance is synergistically reduced when D90 / D50 is 37.9 or more and D2 / D1 is 0.30 or less.
[0015] 1. Negative electrode layer (1)Si-based particles The negative electrode layer contains Si-based particles having pores as a negative electrode active material. FIG. 1 is a schematic cross-sectional view showing an example of the Si-based particle in the present disclosure. As shown in FIG. 1, the Si-based particle 1 has pores 2. In the negative electrode layer, the Si-based particle 1 is bonded to an O element or a functional group R other than an O element on its surface, and therefore has a peak at a predetermined position in FT-IR described later.
[0016] The Si-based particles contain at least Si element. Examples of the Si-based particles include particles of a simple Si element, particles of a Si alloy, and particles of a Si oxide. The Si alloy preferably contains the Si element as a main component. The ratio of the Si element in the Si alloy is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more. Examples of the Si alloy include Si-Li alloys, Si-Al alloys, Si-Sn alloys, Si-In alloys, Si-Ag alloys, Si-Pb alloys, Si-Sb alloys, Si-Bi alloys, Si-Mg alloys, Si-Ca alloys, Si-Ge alloys, and Si-Pb alloys. The Si alloy may be a two-component alloy, or a multi-component alloy of three or more components. The Si alloy may be a Si-Li alloy. Examples of the Si oxide include SiO.
[0017] The Si-based particles have pores. The pores can suppress volume changes during charging and discharging. The porosity of the Si-based particles is not particularly limited, but is, for example, 5% or more and 50% or less. The porosity can be calculated, for example, by observing a scanning electron microscope (SEM) image of the cross section of the Si-based particles and using the following formula. Porosity (%) = 100 × (pore area) / (particle area)
[0018] The Si-based particles may have a predetermined BET specific surface area. The BET specific surface area of the Si-based particles is, for example, 20.0 m 2 / g or more, and 25.0m 2 / g or more, and 2 / g or more, 2 On the other hand, the BET specific surface area of the Si-based particles may be, for example, 60.0 m 2 / g or less, 55.0m 2 / g or less, and 2 / g or less, and 2 / g or less, and 2 The BET specific surface area can be calculated, for example, by the BET method using a pore size distribution measuring device.
[0019] In the Si-based particles, the ratio of particle diameter D90 to particle diameter D50 (D90 / D50) is in a predetermined range. The lower limit of D90 / D50 is usually 37.9 or more, and may be 50.0 or more, or 100.0 or more. On the other hand, the upper limit of D90 / D50 is not particularly limited, but may be, for example, 300.0 or less, 250.0 or less, 200.0 or less, or 150.0 or less. The particle diameter D50 refers to the cumulative 50% particle diameter in the volume-based particle diameter distribution measured by a laser diffraction particle size distribution measuring device. The particle diameter D90 refers to the cumulative 90% particle diameter in the volume-based particle diameter distribution measured by a laser diffraction particle size distribution measuring device.
[0020] The D50 of the Si-based particles is not particularly limited as long as it satisfies the above relationship. The D50 is, for example, 0.3 μm or more, may be 0.4 μm or more, or may be 0.5 μm or more. On the other hand, the D50 is, for example, 1.0 μm or less, may be 0.8 μm or less, or may be 0.6 μm or less.
[0021] The D90 of the Si-based particles is not particularly limited as long as it satisfies the above relationship. The D90 is, for example, 10 μm or more, may be 30 μm or more, or may be 50 μm or more. On the other hand, the D90 is, for example, 100 μm or less, may be 80 μm or less, or may be 60 μm or less.
[0022] The Si-based particles have a peak at 1050 cm -1 Peak A and 1400 cm -1 Peak A is a peak derived from a Si-O bond on the surface of the Si-based particle. Peak B is a peak derived from a Si-R bond (R is a functional group other than O) on the surface of the Si-based particle. The positions of peak A and peak B are within ±100 cm. -1 In addition, the Si-based particles in the present disclosure may have a molecular weight of 1560 cm or less. -1 Near and 870cm -1 It may have a typical peak nearby.
[0023] Furthermore, the Si-based particles have a predetermined range of the ratio (D2 / D1) of the intensity D2 of the peak B to the intensity D1 of the peak A. The upper limit of D2 / D1 is usually 0.30 or less, and may be 0.25 or less, or may be 0.20 or less. On the other hand, the lower limit of D2 / D1 is not particularly limited, but may be, for example, 0.10 or more, or may be 0.15 or more.
[0024] D1 at peak A is not particularly limited as long as it satisfies the above relationship. D1 is, for example, 0.0180 or more and 0.0250 or less. D2 at peak B is not particularly limited as long as it satisfies the above relationship. D2 is, for example, 0.0020 or more and 0.0070 or less. D1 and D2 can be adjusted by changing the manufacturing conditions of the Si-based particles, for example, as shown in the examples described later.
[0025] The content of the Si-based particles in the negative electrode layer is, for example, 50% by weight or more and 95% by weight or less.
[0026] (2) Negative electrode layer The negative electrode layer may contain a solid electrolyte, such as an inorganic solid electrolyte, such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte.
[0027] Examples of the sulfide solid electrolyte include solid electrolytes containing Li, X (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O and halogen. Examples of the halogen include F, Cl, Br, and I. The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. Examples of the sulfide solid electrolyte include Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2.
[0028] The negative electrode layer may contain a conductive material. The use of the conductive material improves the electronic conductivity of the negative electrode layer. Examples of the conductive material include carbon materials. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF).
[0029] The negative electrode layer may contain a binder. Examples of the binder include fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0030] 2.All-solid-state battery The negative electrode layer in the present disclosure is used in an all-solid-state battery. FIG. 2 is a schematic cross-sectional view showing an example of an all-solid-state battery in the present disclosure. The all-solid-state battery 10 shown in FIG. 2 has a positive electrode layer 11, a negative electrode layer 12, and a solid electrolyte layer 13 disposed between the positive electrode layer 11 and the negative electrode layer 12. The all-solid-state battery 10 also has a positive electrode current collector 14 that collects current from the positive electrode layer 11, and a negative electrode current collector 15 that collects current from the negative electrode layer 12. The negative electrode layer 12 is the above-mentioned negative electrode layer.
[0031] (1) Negative electrode layer The negative electrode layer is similar to that described in "1. Negative electrode layer," and therefore will not be described here.
[0032] (2) Positive electrode layer The positive electrode layer contains at least a positive electrode active material. The positive electrode layer may further contain at least one of a solid electrolyte, a conductive material, and a binder. The solid electrolyte, the conductive material, and the binder are the same as those described in "1. Negative electrode layer", so the description here is omitted.
[0033] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 3 / 5 Co 1 / 5 Mn 1 / 5 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 , Li(Ni 0.5 Mn1.5 )O4 and the like; and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0034] The thickness of the positive electrode layer is, for example, not less than 0.1 μm and not more than 1000 μm.
[0035] (3) Solid electrolyte layer The solid electrolyte layer is a layer containing at least a solid electrolyte, and may further contain a binder. The solid electrolyte and the binder are the same as those described in "1. Negative electrode layer", so the description here is omitted. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.
[0036] (4) Other materials An all-solid-state battery usually has a positive electrode current collector that collects the positive electrode layer and a negative electrode current collector that collects the negative electrode layer. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. In addition, the all-solid-state battery in the present disclosure may have a battery case that houses the above-mentioned negative electrode layer, positive electrode layer, and solid electrolyte layer.
[0037] (5) All-solid-state battery The all-solid-state battery is preferably an all-solid-state lithium battery. The all-solid-state battery can be used as a power source for vehicles such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), electric vehicles (BEV), gasoline-powered vehicles, and diesel-powered vehicles. The all-solid-state battery of the present disclosure can also be used as a power source for moving objects other than vehicles (for example, railroads, ships, and aircraft), and can also be used as a power source for electrical appliances such as information processing devices.
[0038] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0039] [Example 1] (Preparation of porous Si particles) The particles of Si alone (27.7 g) were pulverized by a ball mill to adjust the particle size. The conditions of the ball mill were 1000 rpm and 3 h. Next, the crushed Si alone particles and metallic Li (32.5 g) were added to a mortar and mixed at room temperature to obtain a LiSi alloy. The conditions of the mortar mixing were 50 rpm and 20 min. Then, the LiSi alloy was added to the mesitylene solvent (600 ml), and while stirring at room temperature and 250 rpm, a total of 600 ml of ethanol below 0 ° C was dropped at a constant rate (1 drop / 5 sec). Furthermore, while stirring at 250 rpm, a total of 800 ml of acetic acid was dropped. The obtained solution was filtered under reduced pressure conditions to collect the powder. The collected powder was vacuum dried (-0.1 MPa, 12 h or more) to remove the solvent. After that, it was further subjected to thermal drying (160 ° C, 12 h). As a result, Si-based particles having pores (porous Si particles) were obtained.
[0040] (Preparation of negative electrode) The above porous Si particles were added in an amount of 50 mass%, sulfide solid electrolyte (10LiI-15LiBr-75 (0.75Li2S-0.25P2S5)) in an amount of 37 mass%, conductive material (VGCF) in an amount of 10 mass%, and binder (PVdF) in an amount of 3 mass% to a dispersion medium (heptane). This dispersion medium was subjected to ultrasonic treatment for 5 minutes using an ultrasonic homogenizer to obtain a negative electrode mixture. The negative electrode mixture was applied to both sides of a current collector foil (Ni foil, thickness 24 μm) and dried, and then roll pressed at a linear pressure of 50 kN / cm. The obtained current collector foil with a negative electrode layer (thickness of each layer: 45.3 μm) was punched out to φ11.3 mm (1 cm 2As a result, a negative electrode was obtained in which a negative electrode layer was formed on both sides of the negative electrode current collector foil.
[0041] (Preparation of evaluation battery) Cathode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A dispersion medium (heptane) was charged with 84.7% by mass of 02O2, 13.4% by mass of sulfide solid electrolyte (10LiI-15LiBr-75 (0.75Li2S-0.25P2S5)), 1.3% by mass of conductive material (VGCF), and 0.6% by mass of binder (PVdF). The dispersion medium was subjected to ultrasonic treatment for 5 minutes using an ultrasonic homogenizer to obtain a positive electrode composite. The positive electrode composite was applied to a current collector foil (Al foil, thickness 10 μm) and dried, and then roll pressed at a linear pressure of 50 kN / cm. The obtained current collector foil with the positive electrode layer (thickness 70.0 μm) was punched out to φ11.3 mm (1 cm 2 ) As a result, a positive electrode having a positive electrode current collector foil and a positive electrode layer was obtained.
[0042] A sulfide solid electrolyte (10LiI-15LiBr-75 (0.75Li2S-0.25P2S5)) was added to a dispersion medium (heptane) in an amount of 99.5 mass% and a binder (PVdF) was added to a dispersion medium (heptane) in an amount of 0.5 mass%. This dispersion medium was subjected to ultrasonic treatment for 5 minutes using an ultrasonic homogenizer to obtain a composite material. The obtained composite material was applied to a substrate (Al foil, thickness 20 μm) to a thickness of 15 μm, dried, and then punched out to a diameter of φ11.3 mm (1 cm 2 ) As a result, a solid electrolyte layer (separator layer, thickness 15.0 μm) was obtained.
[0043] The positive electrode, separator layer, and negative electrode were stacked together with their centers aligned, and a surface pressure of 5 tons / cm was applied. 2 The layers were then sealed with a tabbed laminate and restrained at 5 MPa. This resulted in the production of an evaluation battery (all-solid-state lithium battery). The evaluation battery was produced so that its capacity was 2 mAh. The porosity of the positive electrode layer and the negative electrode layer were 3.7 g / cc and 1.8 g / cc, respectively.
[0044] [Comparative Example 1] A negative electrode and a battery for evaluation were prepared in the same manner as in Example 1, except that in the preparation of the negative electrode of Example 1, particles of simple Si (Si-based particles having no voids) were used instead of the porous Si-based particles.
[0045] [Examples 2 to 6, Comparative Examples 2 to 8] The conditions of the ball mill were changed to adjust the particle size as shown in Table 1. In addition, at least one of the amount of mesitylene, the temperature of ethanol, the dropping speed of ethanol, the amount of ethanol, and the rotation speed of the stirrer was changed to produce porous Si-based particles having the surface characteristic parameters as shown in Tables 1 and 2. A negative electrode and a battery for evaluation were produced in the same manner as in Example 1, except that the porous Si-based particles were used.
[0046] [evaluation] (Measurement of particle size and BET specific surface area) The D50 and D90 were measured for the Si-based particles produced in each Example and Comparative Example. Specifically, the Si-based particles were dispersed in a water solvent by a wet method, and measured using a laser diffraction particle size distribution measuring device (SALD-2300, manufactured by SHIMADZU). The shape parameter (D90 / D50) was calculated from the obtained D50 and D90. The results are shown in Tables 1 and 2. In Tables 1 and 2, np-Si indicates Si-based particles having voids.
[0047] In addition, the specific surface area of each Si-based particle was determined by the BET method using a specific surface area measuring device (Quantachrome Nova, manufactured by Anton Paar QuantaTec). The results are shown in Tables 1 and 2.
[0048] (FT-IR measurement) The Si-based particles produced in each of the Examples and Comparative Examples were subjected to FT-IR measurement using a Fourier transform infrared spectroscopic hardness meter (Shimadzu Corporation, IRTracer-100) to measure the hardness at 1050 cm -1 The intensity of peak A obtained near D1 and 1400 cm -1The intensity D2 of peak B obtained around 1583.560 cm was measured. The surface characteristic parameter (D2 / D1) was calculated from the obtained value. The results are shown in Tables 1 and 2. In the FT-IR measurement, the smoothing points were set to about 15. Multi-point baseline correction was also performed. ATR correction was performed at 1583.560 cm. -1 was set to.
[0049] (Battery resistance measurement) For the all-solid-state batteries for evaluation obtained in each Example and Comparative Example, DCIR measurements were performed under the following two conditions to determine the charging resistance. The results are shown in Tables 1 and 2. Condition 1: Charge for 10 seconds at SOC 76% Condition 2: Charge for 10 seconds at SOC 40%
[0050] Moreover, for Examples 1 to 6 and Comparative Examples 2 to 8, the relationship between the shape parameter (D90 / D50) and the surface characteristic parameter (D2 / D1) is summarized in FIG.
[0051] [Table 1]
[0052] [Table 2]
[0053] As shown in Tables 1 and 2, it was confirmed that the larger the shape parameter (D90 / D50), the lower the DCIR tends to be. From this, it is presumed that a particle size distribution with a higher standard deviation is more effective at reducing resistance, and that resistance is affected if the total particle surface area is too large. In addition, it was confirmed that the smaller the surface characteristic parameter (D2 / D1) the lower the DCIR tends to be. From this, it is presumed that a large amount of Si-R bonds relative to Si-O bonds on the surface of Si-based particles affects resistance.
[0054] 3, in Comparative Example 5, although the shape parameter was large, the surface characteristic parameter was also large, resulting in a large DCIR value, and in Comparative Example 3, although the surface characteristic parameter was small, the shape parameter was large, resulting in a large DCIR value. This shows that in Si-based particles having pores, controlling both the shape parameter and the surface characteristic parameter is highly correlated with a reduction in battery resistance. [Explanation of symbols]
[0055] 1...Si-based particles 2...pores 10...All-solid-state battery 11 ... Positive electrode layer 12 ... Negative electrode layer 13...Solid electrolyte layer 14...Positive electrode current collector 15...Negative electrode current collector
Claims
[Claim 1] A negative electrode layer for use in an all-solid-state battery, the negative electrode layer contains Si-based particles having pores as a negative electrode active material, The ratio (D90 / D50) of the particle diameter D90 of the Si particles to the particle diameter D50 of the Si-based particles is 37.9 or more; The Si-based particles have a wavelength of 1050 cm in Fourier transform infrared spectroscopy (FT-IR). -1 Peak A and 1400 cm -1 and peak B in the vicinity, A ratio (D2 / D1) of an intensity D2 of the peak B to an intensity D1 of the peak A is 0.30 or less.
Citation Information
Patent Citations
Siox / si / c composite material, method for producing the same, and negative electrode for lithium ion battery containing the composite material
JP2016522139A
Electrode material and its use in lithium-ion batteries
JP2016522560A
Electrode active materials used in metal ion batteries
JP2018514056A
Silicon Particle-Containing Anode Material for Lithium-Ion Batteries
JP2018530859A
Silicon nanoparticle-containing hydrogen polysilsesquioxane, calcined product thereof, and method for producing said polysilsesquioxane and said calcined product
WO2018003150A1
